Colony-Stimulating Factors on Mobilizing CD34+ Cells and Improving Neurological Functions in Patients With Stroke: A Meta-Analysis and a Systematic Review - Chen, Xiuqi; Sun, Wenbo; Zhong, Ping; Wu, Danhong (Frontiers in Pharmacology, 2021)
Background & Purpose—CSF therapy is considered as a promising therapeutic ap-proach for stroke. We performed the meta-analysis to explore the safety and efficacy of CSF in published clinical stroke studies. Methods—We searched articles online and manually. Two reviewers selected studies independently, data on study quality, characteristics of intervention (administration time, observation time, type, dose and injection approach of CSF) and baseline char-acteristics of patients (age, sex, hypertension, diabetes, smoker and lipids) were ex-tracted. Main prognosis outcomes were measured as all-cause death in severe adverse events (SAE) and recurrent stroke in SAE. Secondary outcomes were measured as CD34+ cell counts in periphery blood at day 5, National Institutes of Health Stroke Scale (NIHSS), and Barthel index (BI), Side effects of CSF were taken as the indica-tor of safety. STATA13 software was used to perform the meta-analysis. Results— This meta-analysis involves 485 patients from 8 studies. Among them, 475 patients from 7 studies were gauged SAE (all-cause death), 393 patients from 6 stud-ies were checked SAE (recurrent stroke); 137 patients from 3 studies underwent CD34+ measurement, 389 patients from 6 studies were tested NIHSS and 307 pa-tients from 5 studies were accessed BI. Compared with control group, both all-causes death (RR= 1.73, 95%CI= (0.61, 4.92), P=0.735, I2=0.0%) and recurrent stroke (RR= 0.43, 95%CI= (0.14, 1.32), P=0.214, I2=33.1%) presents no statistically differences, indicating the application of CSF do not statistically alter the prognosis of patients with stroke. The application of CSF effectively enhanced CD34+ cell counts in pe-riphery blood at day5 (SMD= 1.23, 95%CI= (0.54, 1.92), P=0.04, I2=69.0%) but did not statistically impact NIHSS (SMD= -0.40, 95%CI= (-0.93, 0.13), P≤0.001, I2=79.7%) or BI (SMD= 0.04, 95%CI= (-0.38, 0.46), P=0.068, I2=54.3%). Conclusions—Our study consolidates the security of CSF administration for its ex-erting no effect on detrimental outcomes. It proves to be effective in elevating CD34+ cell counts in periphery blood as day5 as well, indicating CSF may partici-pate in stroke recovery, but its efficacy in stroke recovery remains detection. PROSPERO registration number CRD42020166216.